2018
DOI: 10.5334/ijic.s2317
|View full text |Cite
|
Sign up to set email alerts
|

Perceived quality of care transitions between hospital and the home - a cross sectional study

Abstract: Lindblom, S et al 2018 Perceived quality of care transitions between hospital and the home -a cross sectional study. International Journal of Integrated Care, 18(S2): A317, pp. 1-8, DOI: dx.doi.org/10.5334/ijic.s2317 POSTER ABSTRACT Perceived quality of care transitions between hospital and the home -a cross sectional study 18 th

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Studies about health management and patient safety have also been carried out. [8][9][10] In southern Brazil, a study of patients with chronic diseases reported a moderate CT score. 11 In Brazil, CT strategies are being constructed and adapted; no studies have tested the effectiveness of actions that can be performed during hospitalizations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies about health management and patient safety have also been carried out. [8][9][10] In southern Brazil, a study of patients with chronic diseases reported a moderate CT score. 11 In Brazil, CT strategies are being constructed and adapted; no studies have tested the effectiveness of actions that can be performed during hospitalizations.…”
mentioning
confidence: 99%
“…Care transition was analyzed using a construct, the Care Transitions Measure (CTM), mainly at the international level. Studies about health management and patient safety have also been carried out 8–10 . In southern Brazil, a study of patients with chronic diseases reported a moderate CT score 11 .…”
mentioning
confidence: 99%
“…(21) Estudo realizado para avaliar a qualidade da TC do hospital para a casa, verificou que 24% dos pacientes tinham conhecimento insuficiente sobre sua saúde e 29% não tinham informações por escrito compreensíveis sobre os planos após a alta. (31) Foi observada menor pontuação pelos idosos ou responsáveis pela gestão do cuidado em relação às orientações, a respeito das consultas e exames clínicos que deveriam ser feitos nas semanas seguintes após a alta. Apenas 50% dos participantes relataram que receberam uma lista por escrito, legível e de fácil compreensão, das medidas que deveriam ser tomadas após a alta hospitalar.…”
Section: Discussionunclassified